Ever-increasing emergence of multi-drug resistant Staphylococcus pseudintermedius in the dog and its zoonotic potentials - PAPADOGIANNAKIS (Ε. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ), E.; VELONAKIS (E. ΒΕΛΟΝΑΚΗΣ), E.; VATOPOULOS (Α. ΒΑΤΟΠΟΥΛΟΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Methicillin-resistant Staphylococcus pseudintermedius (MRSP) has emerged as an important pathogen in the dog over the past 10 years with an ever increasing incidence worldwide. This review focuses mainly on the epidemiology and detection of MRSP, emphasizing on the interpretation and pitfalls of screening laboratory tests and antimicrobial susceptibility tests. Risk factors for colonization and infection with MRSP and molecular analysis of the dominant clonal lineages are also described. The zoonotic potential and worldwide epidemiology of multidrug resistant Staphylococcus pseudintermedius (MDRSP) are presented. Finally, control options for the colonization of healthy dogs as well as infection by MRSP and MDRSP are described emphasizing on the indications for bacterial culture and susceptibility testing and the principles of topical therapy which may prove to be the sole effective treatment in several canine pyoderma cases.